When nerves hit: The effect of trait anxiety, situational stress, and task mastery on the perception and interpersonal accuracy of musical expressiveness - Chang-Arana, Álvaro M.; Mavrolampados, Anastasios; Pokki, Niklas; Thompson, Marc R. (Frontiers in Psychology, 2023)
Music performance anxiety (MPA) is a prevalent phenomenon with potentially serious consequences to a musician’s wellbeing and professional career. Yet, MPA does not always affect performance quality. It is hypothesized that trait anxiety, situational stress, and task mastery can exacerbate the effects of MPA and affect performance quality. Furthermore, it is unclear whether these effects are noticeable to both listeners and performing musicians. We measure performance quality as the expressiveness scores assigned by musicians and listeners to a set of pre-recorded performances. We selected three pianists with low, mid, and high MPA. Each pianist performed two pieces of their choice, familiar and unfamiliar, which were performed in rehearsal and recital conditions. The performances were videoed and edited into shorter clips for being presented to the performing pianists and to a set of online raters. Listeners and pianists will be asked to rate the expressiveness of all clips. We will determine the difference between the listeners’ perceived expressiveness and the pianists’ own expressiveness scores to estimate how well did listeners understand the pianists’ expressive intentions. We investigate (1) what is the effect of trait anxiety, situational stress, and task mastery on the listener’s perception of expressiveness and (2) what is the effect of these same variables on the listeners’ understanding of expressiveness.